2019
DOI: 10.3762/bjnano.10.29
|View full text |Cite
|
Sign up to set email alerts
|

Heating ability of magnetic nanoparticles with cubic and combined anisotropy

Abstract: The low frequency hysteresis loops and specific absorption rate (SAR) of assemblies of magnetite nanoparticles with cubic anisotropy are calculated in the diameter range of D = 20–60 nm taking into account both thermal fluctuations of the particle magnetic moments and strong magneto–dipole interaction in assemblies of fractal-like clusters of nanoparticles. Similar calculations are also performed for assemblies of slightly elongated magnetite nanoparticles having combined magnetic anisotropy. A substantial dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
55
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(61 citation statements)
references
References 34 publications
4
55
0
Order By: Relevance
“…As a result, the SAR value of the assembly significantly decreases [ 26 , 27 , 60 ] due to the influence of a strong magnetic dipole interaction between the nanoparticles of the cluster. Recent theoretical calculations show [ 54 , 55 ] that with an increase in the average density of a nanoparticle assembly in the range η = 0.01–0.35, the maximum SAR value of the assembly of nanoparticles with different types of magnetic anisotropy decreases by about 5–6 times, compared with the SAR of dilute assembly of the same nanoparticles. Thus, the strong magneto-dipole interaction between the nanoparticles, generally speaking, negatively affects the ability of the assembly to absorb the energy of AC magnetic field [ 1 , 26 , 27 , 54 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, the SAR value of the assembly significantly decreases [ 26 , 27 , 60 ] due to the influence of a strong magnetic dipole interaction between the nanoparticles of the cluster. Recent theoretical calculations show [ 54 , 55 ] that with an increase in the average density of a nanoparticle assembly in the range η = 0.01–0.35, the maximum SAR value of the assembly of nanoparticles with different types of magnetic anisotropy decreases by about 5–6 times, compared with the SAR of dilute assembly of the same nanoparticles. Thus, the strong magneto-dipole interaction between the nanoparticles, generally speaking, negatively affects the ability of the assembly to absorb the energy of AC magnetic field [ 1 , 26 , 27 , 54 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…The thermal fields acting on various nanoparticles of the chain are statistically independent, with the following statistical properties [ 49 ] of their components where k B is the Boltzmann constant, δ α β is the Kroneker symbol, and δ ( t ) is the delta function. The numerical simulation procedure is described in details in [ 54 , 55 ].…”
Section: Model and Methodsmentioning
confidence: 99%
“…The results presented here have the potential to be applied in several fields that use colloidal magnetic nanoparticle systems, in particular the biomedical field [ 36 41 ]. The theoretical and experimental investigation of nanoparticles with magnetic hyperthermia properties is essential for the development of alternative therapies for treating cancer in its various stages and types.…”
Section: Discussionmentioning
confidence: 99%
“…While most experimental and theoretical studies on magnetocrystalline anisotropy have been conducted on bulk and with thin film materials [ 15 , 16 , 17 , 18 ], very few studies have been reported on magnetic nanoparticles. Although the effect of the uniaxial magnetic anisotropy of magnetic nanoparticles on the SLP has been studied theoretically [ 19 ], it is important to evaluate the magnetocrystalline anisotropy of magnetic nanoparticles according to experimentally evaluated characteristics.…”
Section: Introductionmentioning
confidence: 99%